Penerapan Kurikulum dalam Menghadapi Perkembangan Zaman di Jawa Tengah - Devi Erlistiana; Nur Nawangsih; Farchan Abdul Aziz; Sri Yulianti; Farid Setiawan (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
In the current era of globalization, the curriculum is increasingly needed by all elements of society. This can be started in human resources since they were young to human resources who have aged. Intelligence is the intelligence possessed by a person. A person's intelligence grows from within each individual starting from heredity to one's patience in exploring a science seriously. Every human being is required to study at least from elementary to high school / vocational school. In the world of education, various components will be found to support each element so that it can run, one of which is the curriculum. This article will review the application to support the formation of curriculum designs in accordance with current developments, which aims to develop quality and existence, especially in the scope of education.